Combining Price and Quantity Controls under Partitioned Environmental Regulation - Jan Abrell; Sebastian Rausch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyzes hybrid emissions trading systems (ETS) under partitioned environmental regulation when firms' abatement costs and future emissions are uncertain. We show that hybrid policies that introduce bounds on the price or the quantity of abatement provide a way to hedge against differences in marginal abatement costs across partitions. Price bounds are more efficient than abatement bounds as they also use information on firms' abatement technologies while abatement bounds can only address emissions uncertainty. Using a numerical stochastic optimization model with equilibrium constraints for the European carbon market, we find that introducing hybrid policies in EU ETS reduces expected excess abatement costs of achieving targeted emissions reductions under EU climate policy by up to 89 percent. We also find that under partitioned regulation there is a high likelihood for hybrid policies to yield sizeable ex-post cost reductions.
Keywords: H23; Q54; C63; 330